MEMBANGUN COMMUNICATION SKILL BAGI MURID DAN GURU PKBM NEGERI 23 JAKARTA PUSAT - Damdam Damiyana; Retno Widowati; Ali Zulfikar; Kania Farida; Minggu Minggu; Aris Hendrawan (JURNAL ABDIMAS PLJ, 2022)
Having communication skills is important for everyone, especially for students who are still learning to get knowledment. The importance of the ability to communicate for students is one of the means of supporting the success of students' achievements in learning. Implementation activities to build communication skills for students and teachers at PKBM Negeri 23 Jakarta went smoothly as planned. Starting from the speech of the head of PKBM, the delivery of materials and communication practices can be carried out properly, although it is carried out gradually and slowly. The disciples can absorb everything that has been well conveyed. With frequent training like this, it is hoped that students and teachers can improve techniques to build effective communication skills. Be a qualified person with communication. Understand how to manage emotions positively to build effective communication between members of the organization. Improve the quality of work and strengthen team performance.Keywords: Training, Community Service, Communication Skills.